Integrating E-Procurement and Good Governance for Fraud Prevention in Public Procurement: Evidence from Banyuasin Regency, Indonesia - Evada Dewata; Eka Jumarni Fithri; Riza Wahyudi; Farhan Aziz; Arrum Ramadhani; Nurhalizah Rahmah Putri (ccounting Department, Universitas Syiah Kuala, Indonesia, 2026)
This study examines fraud prevention within the Banyuasin Regency Government, Indonesia, by analyzing the roles of e-procurement, good governance, and individual morality. Using an explanatory quantitative approach, data from 123 procurement officials were analyzed using PLS-SEM. The findings show that e-procurement and good governance significantly enhance fraud prevention, while individual morality has no significant direct or moderating effect. The study highlights digital governance and institutional mechanisms as more effective determinants of fraud prevention than individual moral factors. Practically, the findings encourage local governments to strengthen e-procurement systems and governance practices to improve transparency, accountability, and technology-based fraud prevention